A RECONSTRUCTION OF THE CLIMATE AND VEGETATION OF NORTHEASTERN SIBERIA BASED ON LAKE SEDIMENTS - Lozhkin A.V.; Anderson P.A. (My University, 2006)
Detailed palynological analysis of glacial, tectonic, and crater lakes of northeastern Siberia reveals continuous records of the changing vegetation during one or several climatic cycles of the Pleistocene and in the Holocene. The most continuous records in the mountain areas of the region are those of Lake Elikchan-4 (northern Okhotsk Sea Region). Pollen records of Lake El’gygytgyn, which was formed by the impact of a meteorite in the northern Chukchi Peninsula, reflect the response of land vegetation to the global climatic impact during the last 300 ka.
Keywords: Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен